الجمع والطرح والاقواس


(x − 3) − (y − 4)   =   x − 3 − y + 4
 
    =   xy + 1.
 (x + 2) + (y + 8)   =   x + 2 + y + 8
 
    =   x + y + 10.
   (x + 2) − (y + 8)   =   x + 2 − y − 8
 
    =   xy − 6.
   .  (x − 2) + (y + 8)   =   x − 2 + y + 8
 
    =   x + y + 6.
  .  (x − 2) − (y + 8)   =   x − 2 − y − 8
 
    =   xy − 10.
 .  (x − 2) − (y − 8)   =   x − 2 − y + 8
 
    =   xy + 6.
  .  (x − 2) + (y − 8)   =   x − 2 + y − 8
 
    =   x + y − 10.
   .  (a − 2) + (b + 3) − (c − 7)   =   a − 2 + b + 3 − c + 7
 
(a − 5) − (b + 6) − (c − 9)   =   a − 5 − b − 6 − c + 9
 
    =   abc − 2.
  (a + 2) − (b − 3) + (c − 8) − (d + 1)
 
    =   a + 2 − b + 3 + c − 8 − d − 1
 
    =   ab + cd − 4.

 

Welcome To My Website
hassan.ab.ma © 2017.Free Web Site